'I don't really know where I stand because I don't know if I took something away from her': Moral injury in South African speech–language therapists and audiologists due to patient death and dying. Issue 1 (4th August 2022) - Nagdee, Nabeelah; Manuel de Andrade, Victor
Abstract: Background: Speech–language therapists and audiologists (SLT&As) may encounter difficulties when confronted with patient death and dying, which may conflict with their moral beliefs and result in moral injury. Furthermore, South African SLT&As practice in a country with a high mortality rate, which may add to the complexity of their experience. Moreover, they may be influenced by African philosophies promoting care, which might conflict with their experiences of patient death and dying. Aims: To explore the moral injury experienced by South African SLT&As in patient death and dying, and how they overcame the injury. Methods & Procedures: This article forms part of a larger qualitative study that explored SLT&As' experiences of patient death and dying in South Africa. Thematic analysis was conducted on the transcripts of 25 episodic narrative interviews conducted with South African SLT&As on their experiences of patient death and dying. Outcomes & Results: Findings suggest that South African SLT&As experienced helplessness, guilt and anger in patient death and dying. However, with support from the allied team, engaging in self‐reflection and religious practices, they reported alleviation of moral injury. Conclusions & Implications: In order to mitigate moral injury in South African SLT&As, they require professional education, self‐care strategies, guidelines and support from the teams in which they work and their supervisors. Research is needed that explores how SLT&As' biographical characteristics and interactions with significant others of dying and deceased patients, may result in moral injury. What this paper adds?: What is already known on this subject?: Moral injury and measures used to overcome the injury have been explored in military personnel, doctors and nurses, but not in SLT&As. However, studies that explored the perceptions of SLTs and/or audiologists regarding providing palliative care and of death and dying, particularly that by Rivers et al. in 2009, suggested that these professionals may be at risk of experiencing emotional trauma due to patient death, particularly when not receiving undergraduate education on this subject. However, the extent of this trauma and the support needed to overcome it is unknown because the participants in these studies may have not experienced patient death, and were only students or just SLTs. What this article adds?: This article highlights the complexity of speech–language therapy and audiology practice when confronted with patient death and dying. South African SLT&As may have to make decisions that conflict with their morals and professional practice standards, especially as the helping nature of their profession is characterized by African philosophies that promote care, which may result in moral injury. Clinical implications of this article: This article indicates that in addition to undergraduate education on patient death and dying, SLTs and audiologists require continuous professional education on this topic, self‐care strategies, support from the teams in which they work, and their supervisors and guidelines for when they encounter patient death and dying.